Identification of Inhibiting Factors in Triple Helix Collaboration in the Commercialization Process at a Private University in Indonesia - Sisca Eka Fitria; Stephanie Putri Reinda (Cita konsultindo, 2024)
Collaboration between a university, industry, and government (Triple Helix) in supporting commercialization still faces obstacles. The goal of this research is to identify the inhibiting factors of Triple Helix collaboration in commercialization at a private university in Indonesia. The method used is qualitative with a descriptive and case study approach. The research findings show that the university plays a role as a provider of research and innovation. The industry plays roles as an idea generator, early adopter, producer, capital provider, and end user. The government acts as a regulator, funding provider, innovation user, research partner, and collaboration facilitator. Inhibiting factors from the university include limited incentives, differences in goals with the industry, and a lack of experts. From the industry perspective, obstacles include dependence on foreign technology, insufficient understanding of the university's capacity, and a dynamic market. From the government’s perspective, obstacles include ineffective policies, limited budget allocation, and suboptimal coordination. To address these inhibiting factors, the university needs to improve internal coordination, optimize commercialization schemes, increase the number of experts, and develop industrial gathering activities. The industry should better understand academic needs, increase funding allocation, and adopt Open Innovation approaches. The government needs to enhance collaboration activities, research funding, streamline administrative processes, and create a comprehensive commercialization scheme. This research provides a deep understanding of the inhibiting factors of Triple Helix collaboration in commercialization at a private university in Indonesia.